Divides
an integer is divisible by another integer
m
if there exists an integer
k
such
that
n
=
k
⋅
m
. If this is all true we write
m
|
n
.
Divisible iff Integer Quotient
Suppose that
a
∣
b
iff
b
a
∈
Z
Suppose that
a
∣
b
, then there is some
k
∈
Z
such that
a
⋅
k
=
b
therefore
k
=
b
a
, and since
k
∈
Z
then
b
a
∈
Z
as needed.
n Factorial is Divisible by Its Factors
For any
k
∈
[
1
,
…
,
n
]
k
∣
n
!
n
!
=
1
⋯
k
⋯
n
therefore
n
!
k
=
1
⋯
(
k
k
)
⋯
n
∈
Z
so
therefore
k
∣
n
!
Not Divisible iff Non-Integer Quotient
a
∤
b
iff
b
a
∉
Z
By the fact that
P
⟺
Q
iff
¬
P
⟺
¬
Q
1 Divides Everything
Suppose that
j
∈
Z
, then
1
|
j
If something Divides One then it is One or Negative One
Suppose
d
∣
1
then
d
=
±
1
We have that
1
=
k
d
but the only numbers in
Z
that have a multiplicative inverse are
1
,
−
1
so
d
must be one of those or else we have a contradiction.
If Zero Divides a Number, then that Number is Zero
Suppose
0
∣
d
then
d
=
0
By definition we have
d
=
k
⋅
0
=
0
so
d
=
0
0 is Divisible by Everything
for any
d
∈
Z
,
d
|
0
In the definition of divides take
k
=
0
,
then we can see that
0
=
0
⋅
d
thus we can say that
d
|
0
Everything Divides Itself
Let
a
∈
Z
then
a
∣
a
Clearly
1
⋅
a
=
a
therefore
a
∣
a
Division is Transitive
Suppose
a
∣
b
and
b
∣
c
then
a
∣
c
We have that
b
=
k
a
a
and
c
=
k
b
b
therefore
c
=
k
b
(
k
a
a
)
therefore by taking
k
c
=
(
k
a
k
b
)
we see that
a
∣
c
If you Divide a Number, then You Divide their Multiples
For any
a
,
b
,
c
∈
Z
a
∣
b
⟹
a
∣
b
c
Suppose that
a
∣
b
therefore there is
k
∈
Z
such that
b
=
k
a
, therefore multiply both sides to get
b
c
=
(
k
c
)
a
and therefore
a
∣
b
c
as needed.
If it Divides it's Less than or Equal with Absolute Values
Suppose that
n
,
d
∈
Z
, such that
n
≠
0
then if
d
divides
n
, then
|
d
|
≤
|
n
|
We see that
n
=
k
d
for some
k
∈
Z
, since
n
≠
0
then also we must have
k
,
d
≠
0
specifically note that
|
k
|
≥
1
so that we have
|
n
|
=
|
k
d
|
=
|
k
|
⋅
|
d
|
≥
1
|
d
|
=
|
d
|
so that
|
n
|
≥
|
d
|
We have to specify
n
≠
0
because we know that everything divides zero, and therefore without that assumption we could use it to claim that since
−
42
∣
0
that
|
−
42
|
≤
0
which is clearly false.
Larger Absolute value Implies no Division
for any
n
,
d
∈
Z
such that
n
≠
0
if
|
d
|
>
|
n
|
then
d
∤
n
If two Numbers Divide each other then Their Absolute Values are Equal
For any
a
,
b
∈
Z
, if
a
∣
b
and
b
∣
a
then
|
a
|
=
|
b
|
If
a
=
0
then because
a
∣
b
then this forces
b
=
0
so that
a
=
b
=
0
, also if we assumed
b
=
0
the same thing occurs.
In the case that neither of
a
,
b
=
0
then recall that if
a
∣
b
we have
|
a
|
≤
|
b
|
also since
b
∣
a
then also
|
a
|
≤
|
b
|
so that
|
a
|
=
|
b
|
.
If a Number Divides another Then Given a Common Factor Their Quotients Divide Each Other
Suppose that
a
,
b
,
d
∈
N
1
such that
a
∣
b
and that
d
is a common divisor of
a
,
b
, then
a
d
∣
b
d
Divisibility is a Partial Order on the Natural Numbers
Divisibility is a
partial order on
N
0
.
Note that we can't quite get a partial order
Z
because of the fact that
−
a
∣
a
.
Linearity of Division
Suppose that
a
∣
b
1
,
…
,
b
n
then
a
∣
c
1
b
1
+
⋯
+
c
n
b
n
where
a
,
b
i
,
c
i
∈
Z
For the base case of
n
=
2
if
a
∣
b
1
and
a
∣
b
2
then we know that there are
k
1
,
k
2
∈
Z
such that
b
1
=
k
1
a
and
b
2
=
k
2
a
so that
c
1
b
1
+
c
2
b
2
=
c
1
(
k
1
a
)
+
c
2
(
k
2
a
)
=
a
(
c
1
k
1
+
c
2
k
2
)
.
For the induction step, assume the statement holds true for
k
∈
N
1
and we'll show that it holds true for
k
+
1
so suppose that
a
∣
b
1
,
…
b
k
+
1
by the induction hypothesis we know that
a
∣
c
1
b
1
+
⋯
+
c
k
b
k
so we get some
j
′
∈
Z
such that
c
1
b
1
+
⋯
+
c
k
b
k
=
j
′
a
and also some
j
′
′
∈
Z
such that
b
k
+
1
=
j
′
′
a
and therefore
c
1
b
1
+
⋯
+
c
k
b
k
+
c
k
+
1
b
k
+
1
=
j
′
a
+
j
′
′
a
=
a
(
j
′
+
j
′
′
)
so therefore
a
∣
c
1
b
1
+
⋯
+
c
k
+
1
b
k
+
1
Even Number
We say that an integer
n
∈
Z
is even if there is some
k
∈
Z
such that
n
=
2
k
A power of an Even Number is Even
If
n
∈
Z
is even, then for any
m
∈
N
1
we have
n
m
is even
If
n
is even then there is some
k
∈
Z
such that
n
=
2
k
and therefore
n
m
=
(
2
k
)
m
=
2
m
k
m
=
2
(
2
m
−
1
k
m
)
so that
n
m
is also even.
Odd Number
We say that an integer
n
∈
Z
is odd if there is some
k
∈
Z
such that
n
=
2
k
+
1
A power of an Even Number is Odd
If
n
∈
Z
is odd, then for any
m
∈
N
0
we have
n
m
is odd
Base case, set
m
=
0
then
n
m
=
1
which is odd. For the induction step assume it holds true for
k
∈
N
0
so that
n
k
is odd, which means that there is some
j
∈
Z
such that
n
k
=
2
j
+
1
therefore
n
k
+
1
=
(
2
j
+
1
)
n
but
n
is odd so there is some
j
′
∈
Z
such that
n
=
2
j
′
+
1
and thus
n
k
+
1
=
(
2
j
+
1
)
(
2
j
′
+
1
)
=
4
j
j
′
+
2
j
+
2
j
′
+
1
=
2
(
2
j
j
′
+
j
+
j
′
)
+
1
hence
n
k
+
1
is prime so the statement follows from the principle of induction.
Product of Two Equal Factors means They are Square Roots
Suppose that
a
=
b
c
then
b
=
a
iff
b
=
c
⟹
suppose that
b
=
a
then for sake of contradiction if
b
≠
c
then if
c
<
b
then we see that
a
=
b
c
<
b
b
=
a
a
=
a
which is impossible, on the other hand if
c
>
b
=
a
then we see
a
=
b
c
<
c
c
<
a
a
which yields the same contradiciton.
⟸
Now suppose that
b
=
c
therefore
a
=
b
c
=
b
b
therefore
b
2
=
a
and so
b
=
a
as needed, moreover in this case note that
c
=
a
as well.
Product Implies Square Root bound on Factors
Suppose that
a
,
b
,
c
∈
N
1
and that
b
≠
c
where
a
=
b
c
then
(
b
>
a
∧
c
<
a
)
∨
(
b
<
a
∧
c
>
a
)
Suppose for the sake of contradiction that it was not true, so that we knew that
(
b
≤
a
∨
c
≥
a
)
∧
(
b
≥
a
∨
c
≤
a
)
Suppose that
b
≤
a
and
b
≥
a
holds true, then
b
=
a
since
c
≠
b
then if
c
<
b
we see that
b
c
<
a
a
=
a
which is a contradiction since we know that
b
c
=
a
, if it turns out that
c
≤
a
and
c
≥
a
it is handeled symetrically.
On the other hand if we know that
b
≤
a
and that
c
≤
a
, since
b
≠
a
then we know that
b
≠
a
, therefore more specifically we see that
b
<
a
this implies that
a
=
b
c
<
a
a
=
a
which is a contradiction. In the case of
c
≥
a
and
b
≥
a
it follows in a symmetrical manner.
Number To the Power m Minus 1 Divides Number To the Power n if m Divides n
Let
a
,
m
,
n
∈
N
1
then
m
∣
n
⟹
(
a
m
−
1
)
∣
(
a
n
−
1
)
We have that
n
=
m
k
for some
k
∈
Z
and we want to prove that
a
m
k
−
1
=
(
a
m
−
1
)
j
for some
j
∈
Z
, a good guess would be that
j
=
a
(
m
−
1
)
k
which produces
(
a
m
−
1
)
(
a
(
m
−
1
)
k
)
=
a
m
k
−
a
(
m
−
1
)
k
and so we have to get rid of the
a
(
m
−
1
)
k
term, which inspires us to try
j
=
a
(
m
−
1
)
k
+
a
(
m
−
2
)
k
which yields
(
a
m
−
1
)
(
a
(
m
−
1
)
k
+
a
(
m
−
2
)
k
)
=
a
k
m
+
a
(
m
−
1
)
k
−
(
a
(
m
−
1
)
k
+
a
(
m
−
2
)
k
)
=
a
k
m
−
a
(
m
−
2
)
k
As we've just run into the same problem as last time we see that adding
a
(
m
−
3
)
k
would remove the most recent residue term, but then leave the new residue term
a
(
m
−
3
)
k
. Therefore formally using induction we can show that
(
a
m
−
1
)
(
∑
i
=
0
m
−
1
a
i
k
)
=
a
m
k
−
1
=
a
n
−
1
where
1
is really the residue term
a
(
0
)
k
a
and that
m
∣
(
a
+
b
)
then
m
∣
b
-->